If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x)(x) + x = 72 Multiply x * x x2 + x = 72 Reorder the terms: x + x2 = 72 Solving x + x2 = 72 Solving for variable 'x'. Reorder the terms: -72 + x + x2 = 72 + -72 Combine like terms: 72 + -72 = 0 -72 + x + x2 = 0 Factor a trinomial. (-9 + -1x)(8 + -1x) = 0Subproblem 1
Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9Subproblem 2
Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8Solution
x = {-9, 8}
| 4x-2+7x+4= | | 5a+12+9a=2a-4a | | P-412=1329 | | 0.01x+1.2=3.2 | | 16x^2+49=-25 | | T=180-(9x+32) | | 80+5x+y=180 | | x+21=86 | | p+412=1329 | | -9b+8+7=-3b+13 | | 2=3(3n+-5)-10 | | 9x+6=33x-6 | | 4.3(2x-3)+2.8=9.5x-3 | | 3(z-3)=5+4z | | 24=6(x+-6)-x | | 5x+6x-2=20 | | 8x+13+2x+7=180 | | -2.6d-0.49=1.79 | | 2-2-2-2-2-2-2+2+x=3 | | p-400=1230 | | 4x-6x-40=0 | | 2-2-2-2-2-2-2-2-2=2 | | 6n-18=4n | | an=7+(n-1)(7) | | x-13=3x-27 | | X(x+10)=90 | | 0.06(y-9)+0.08y=0.18y-0.2 | | 13x+12=8x+7+4x+14 | | x-54=27 | | 55x+200=20+65x | | lnx=0.375 | | 6x^2+24=25x |